If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = -27 + 8x Reorder the terms: 12 + 5x = -27 + 8x Solving 12 + 5x = -27 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 12 + 5x + -8x = -27 + 8x + -8x Combine like terms: 5x + -8x = -3x 12 + -3x = -27 + 8x + -8x Combine like terms: 8x + -8x = 0 12 + -3x = -27 + 0 12 + -3x = -27 Add '-12' to each side of the equation. 12 + -12 + -3x = -27 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -27 + -12 -3x = -27 + -12 Combine like terms: -27 + -12 = -39 -3x = -39 Divide each side by '-3'. x = 13 Simplifying x = 13
| 3+2x=18-3x | | 10-2x=4+x | | 3a-1=7a-9 | | 3x+12=58-2x | | 9a=a+16 | | 5x-4y=19y | | k(x^2-3x+4)+x-3=0 | | f(4x^2+3)=0 | | k^2-k-2=0 | | 7(5-x)=14 | | k^3-k^2-2k-12=0 | | (x-3)(x^3-1)=0 | | x^8=-1 | | 111-5x=13x+23 | | 147-6x=21x+21 | | 4(h*h)+5h=84 | | 6z-12=5 | | 10x-22+5x=3 | | (78).425= | | 5x=3x^2 | | (5x+3)*(24-3x)=0 | | x^2+21x+32=12 | | 8x-8=x+7 | | b=(11b+14)(8-10b) | | 5x+8=3(x+4) | | b=8a(8A-13) | | 8p+p^2=105 | | 8x+19=2x+163 | | b=-(-5a-3)+(-5+8a) | | -3p+2q-3r= | | 3x-7=2x+18 | | 253-3x=42x+23 |